Implikasi Aliran Pragmatisme dalam Pendidikan - Istiqomah, Murniati; Zahru, Fadllul Anisa; Fadhilaturrahmah, Nur Wakhidah (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
Pragmatism as a school of philosophy was first developed in America. The first philosopher to introduce and develop pragmatism was Charles S. Peirce who emphasized human activity and purpose in gaining understanding and knowledge. The American thinker who is very attached to the educational philosophy of pragmatism is John Dewey. Pragmatism as a philosophical school can be understood metaphysically, epistemologically and axiologically.